Responsive Web-Based Inventory Information System Design - Wardana, Dony; Ashari, Mochamad Luqman; Adianto, Adianto (Newinera Publisher, 2025)
Menteng Electricity Company, as a provider of electricity distribution services in the Jakarta area, is obliged to meet occupational safety and health standards to ensure safe and reliable working conditions. However, the lack of inventory optimization results in inconsistent manual recording, scattered facility locations, and minimal data integrity. Therefore, this study aims to design a responsive web-based inventory information system using the Next.js framework, the TypeScript programming language, and a MySQL database. It is equipped with an automatic reminder feature via short message service (SMS) to support regular monitoring. This can reduce human error.